PENGARUH KEMAMPUAN KOGNISI TERHADAP TONUS OTOT MULUT PENDERITA SINDROMA DOWN - Margaretha Suharsini (Faculty of Dentistry, Universitas Indonesia, 2015)
The clinical signs of Down's syndrome patients are mental retardation and muscular hypotonia. It is commonly found oral dysfunction in mental retardation children. The purpose of this study was to know whether in Down's sundrome patients the degree of mental retardation may affect the oral dysfunction caused by their muscular hypotonia. Intelligence Quotient (IQ) and Social Quotient (SQ) were measured to describe cognitive capability in mental retardation children, while oral muscular tone was described by the electromyography examination of the masseter and temporal muscles, oral function was achieved by its exmination scores. The data were subsequently analyzed using the factor analyss and the regression analysis to prove the effect of the cognitive capability to the oral muscular tone. The result showed that the cognitive capability affected the oral muscular tone significantly with p=0.001; b=2.399 and R=0.699. It could be concluded that the cognitive capability greatly affected the oral muscular tone in Down's syndrome patients.